2012
DOI: 10.1093/aob/mcs264
|View full text |Cite
|
Sign up to set email alerts
|

Mastoparan-induced programmed cell death in the unicellular alga Chlamydomonas reinhardtii

Abstract: In C. reinhardtii MP triggered PCD of atypical phenotype comprising features of vacuolar and necrotic cell deaths, reminiscent of the modality of hypersensitive response. It was assumed that depending on the physiological state and sensitivity of the cells to MP, the early cell-death phase might be not mediated by caspase-like enzymes, whereas later cell death may involve caspase-like-dependent proteolysis. The findings substantiate the hypothesis that, depending on the mode of induction and sensitivity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 88 publications
4
47
1
Order By: Relevance
“…Using the cell wall‐deficient C. reinhardtii mutant strain cw15, we were, however, not able to confirm the results of Yordanova et al. (). As shown in the present communication, we observed necrotic cell death in this particular C. reinhardtii strain both after treatment with mastoparan or broad‐range cysteine and serine protease inhibitors.…”
contrasting
confidence: 93%
See 2 more Smart Citations
“…Using the cell wall‐deficient C. reinhardtii mutant strain cw15, we were, however, not able to confirm the results of Yordanova et al. (). As shown in the present communication, we observed necrotic cell death in this particular C. reinhardtii strain both after treatment with mastoparan or broad‐range cysteine and serine protease inhibitors.…”
contrasting
confidence: 93%
“…As reported by Yordanova et al. (), the mastoparan‐induced PCD in C. reinhardtii could be, at least partly, overcome by antioxidants and several broad‐range cysteine and serine protease inhibitors.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Stimulation of PLC has been described previously (3) for rat mast cells and hepatocytes and human HL-60 leukaemia cells, whereas inhibition of PLC has been found for SH-SY5Y human neuro-blastoma cells and human astrocytoma cells (3). Results of recent studies have indicated that there is a possibility of stimulation of programmable cell death in various types of cells (4)(5)(6).…”
Section: Introductionmentioning
confidence: 92%
“…By contrast, the inhibition of PLC by mastoparan has been demonstrated in SH-SY5Y human neuroblastoma cells and in human astrocytoma cells (1). Recent studies suggested the possibility of programmed cell death stimulation in different types of cells (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%